KINERJA PROSES PELELANGAN IKAN DI PASAR ARUMBAI KOTA AMBON - Frendly Matulessy; Dionisius Bawole (Universitas Pattimura, 2017)
This study aims to measure the performance of fish auction process in Arumbai Market in Ambon. Primary data were collected from 43 respondents through observation and direct interview based on questionnaire. Data was analysed by qualitative descriptive method, importance performance analysis method (IPA) and gap analysis, and value for money method. The results show that: 1). There are three auction process activities namely pre auction, auction, and post auction; 2). Fisherman's satisfaction level is 67% and merchant satisfaction is 81%; and 3). The auction performance of the economic aspect is less economical, with the final value of 83%, while the fish auction performance from the efficiency aspect is less efficient with the value of 76%. For that, it needs additional officers to manage fish auction place (TPI) in Arumbai Market. In addition, the fish auction facilities (TPI) in Arumbai Market needs to be improved.